The Use of a Deep Learning Model to Enhance Fifth-Grade Students' Higher-Order Thinking Skills (HOTS) in Mathematics at an Integrated Islamic School in Jambi City - Defriyanti Defriyanti; M.Syahran Jailani; Arif Wiratama (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to describe how to improve fifth-grade students’ HOTS using the Deep Learning Model in Mathematics lessons at an elementary school (SDIT). This study is a Classroom Action Research (CAR) conducted in two cycles, including planning, implementation, observation, and reflection. The subjects of the study were fifth-grade students at Asy-Syifa Alinaraha Integrated Primary School. Data collection was conducted through observation, delamination, and reflection. Data were analyzed using quantitative and qualitative descriptive methods. The results of the study Show that the application of the Deep Learning model to mathematics learning can improve individual students’ abilities. This improvement is evident in the increase in test scores in each cycle. Furthermore, students become more active, have high-level reasoning skills, and are responsible in completing assignments. Therefore, the Deep Learning model is effective in improving fifth-grade students’ HOTS abilities.